THE COMMON STARLING STURNUS VULGARIS L., 1758 REGULAR WINTERING SPECIES IN THE ALGERIAN SAHARA - Chedad Abdelwahab; Adamou Nedjla; Abdelhakim Bouzid; Djamel Bendjoudi; Omar Guezoul (Natural Resources and Sustainable Development, 2022)
The availability of food and climate change are among the causes of range expansion of species, especially birds. During 2016 and 2022, counts were undertaken by direct observation of the Common starling Sturnus vulgaris L., 1758, using a Nikon P900 camera, based on the Progressive Frequency Sampling (Echantillonnage Fréquentiel Progressif “EFP”). The species become a regular visitor at Ghardaïa and an accidental winter visitor at Touggourt during the 6 years of this study. It is observed near water surfaces, in the interior of oases, palm groves and orchards, which contain a lot of fruits, seeds, and even other food sources, the latter have made it possible to force the Starlings to extend slightly to the south in order to spend the winter in these areas. This paper presents a preliminary study of expansion of the Common starling in Algerian Septentrional Sahara.